Subconjunctival Delivery of Antibiotics in a Controlled-Release System A Novel Anti-infective Prophylaxis Approach for Cataract Surgery - Cardillo, Jose A.; Paganelli, Fernando; Melo, Luiz A. S.; Silva, Arnobio A. [UNESP]; Pizzolitto, Antonio Carlos [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (Amer Medical Assoc, 2010)
Objective: To compare the efficacy of subconjunctival injection of a combination of triamcinolone and ciprofloxacin hydrochloride, 2 mg/0.1 mL, in a controlled-release system (DuoCat) with that of ciprofloxacin hydrochloride, 0.3%, eyedrops for infection prophylaxis.Methods: Rabbit eyes were injected subconjunctivally with a combination of triamcinolone and ciprofloxacin hydrochloride, 2mg/0.1 mL, or ciprofloxacin hydrochloride, 2 mg/0.1 mL, alone. The aqueous and vitreous humor pharmacokinetic profiles were compared with those of a single drop of ciprofloxacin hydrochloride, 0.3%, 6 times daily. In 45 rabbits, Staphylococcus aureus was injected into the anterior chamber: 15 randomly received 1 drop of ciprofloxacin hydrochloride, 0.3%, every 4 hours during 24 hours; 15 received drops of balanced salt solution; and 15 received a combination of triamcinolone and ciprofloxacin hydrochloride, 2 mg/0.1 mL. After 24 hours, endophthalmitis scores were recorded, aqueous and vitreous humors underwent culture, and histologic analysis was performed.Results: The combined triamcinolone and ciprofloxacin treatment allowed higher intraocular levels of ciprofloxacin. The median endophthalmitis clinical scores for the combination of triamcinolone and ciprofloxacin and ciprofloxacin-only eyedrop groups were equivalent (P=.42) and were significantly lower than those of the balanced salt solution group (P<.001). The culture was negative for S aureus in the combined triamcinolone and ciprofloxacin and ciprofloxacin eyedrop regimens. No adverse effects were observed with either route.Conclusions: Ciprofloxacin eyedrops and combined triamcinolone and ciprofloxacin were equally tolerated and efficacious. The combined triamcinolone and ciprofloxacin treatment may eliminate noncompliance issues and may prove to be a valuable clinical tool for surgical prophylaxis.Clinical Relevance: The combined triamcinolone and ciprofloxacin treatment may be a new useful strategy for surgical prophylaxis.